The relationship between Affective Commitment and organizational citizenship behavior - Ali, Mohammed Ahmed Al-Khalifa (Arab Journal for Sciences and Research Publishing, 2015)
This study aimed to identify the relationship between Affective Commitment and organizational citizenship behavior. This study hypothesized a statistical significant relationship between Affective Commitment and organizational citizenship behavior. Also, there is a statistical significant relationship between Affective Commitment and (Altruism, Courtesy, Sportsmanship, Civic virtue, Conscientiousness). A questionnaire was used to fulfill the study objectives and to test its hypotheses. Results that had been obtained from (100) employees from Red Sea university had shown that organizational citizenship behavior is highly prevalent among the staff in the Red Sea university. In addition, there is a significant relationship between Affective Commitment and organizational citizenship behavior.